Técnicas metodológicas de natación para el desarrollo de las habilidades motoras en adultos y adultos mayores, en la ciudad de Guaranda, periodo mayo-septiembre 2019 - Chiluiza Nina, Diego Armando (2019)
The project, “METHODOLOGICAL SWIMMING TECHNIQUES FOR THE DEVELOPMENT OF MOTOR SKILLS IN ADULTS, IN THE CITY OF GUARANDA, MAY-SEPTEMBER 2019 PERIOD”, is based on scientific research to generate interest in a new action, which through The practice helps adults discover one more way to improve their motor activity. The research work was carried out with the group of older adults of the “Flor de la Juventud” center of the Guaranda province of Bolivar, to strengthen swimming skills and motor skills, encouraging this group of individuals to practice this sport, based on the fact that It only helps improve your motor activity but also strengthens your knowledge and mastery of your body, this generated a progress in your health. The research, indicates the importance of making a habit of this sport, so that it is a support so that they improve the techniques of swimming teaching, educational methods that are recreational with a sports and integral approach were used; to generate interest and raise cognitive abilities. To create a relationship between adults and older adults and water through application and learning to implement activities such as: setting, floating, breathing, propulsion, so that this group of people have The freedom to move around the pool and overcome the fear of practicing this sport was used observation and account techniques, therefore the research is qualitative. Through this sport, adults and older adults, carried out a completely different activity, implementing freestyle as a starting point to improve their motor skills, according to these guidelines the project was executed with a group of 28 adults and older adults. 50 and 70 years of age, who perish to the aforementioned center of the city of Guaranda, this group regularly attended the La Colina resort, where the teaching and practice activities of this water sport took place. The research is exploratory and descriptive in order to give key answers to the teaching of this sport and to help the physical condition of adults and older adults improve and encourage the practice of sport for recreation, distraction and enjoyment. a moment of different activity that takes them out of the daily routine to what they are used to and improves their quality of life.